Life Insurance in Karnataka: A Colonial Legacy - Sanjana C.P., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
In the history of mankind the concept of “Risk” is not new. To live a better life man has to face more challenges and take risks. Since the birth of civilizations humans have tried to manage different kinds of risks like loss of men and material, health problem, assets etc,. Human’s search for security has led to different ideas and concepts since the ancient times but this was given importance on a large scale only in the modern times. This mostly developed in the western world. With the advent of East India Company, it introduced a number of changes in the political, administrative, economic aspects of the country. Some of it were also taken up by the local princely states which were indirectly under the control of the British. One such state was the Princely state of Mysore. Mysore was under the indirect rule of the British hence any reforms introduced by the British was brought into effect in Princely Mysore state also. By the second half of 1800s many private insurance companies were established in different parts of the country. It was the Dewan of Mysore K Sheshadri Iyer introduced insurance in Mysore for the security of Government officials in 1891.Since then insurance as an industry has been growing both in public and private sectors in Karnataka and in India. The Mysore state life insurance which began in colonial period continues to thrive in Karnataka after independence as a major public sector undertaking providing compulsory insurance for the government employees in the name of Karnataka Government Insurance Department. The concept of modern insurance as a way of risk management and a tool for security of men and material in the state of Karnataka is a form of colonial legacy.
Keywords: Life Insurance; British Administration; Princely Mysore; Mysore State Life Insurance; Karnataka Government Insurance Department